EXPLORING THE NUTRITIONAL AND MINERAL COMPOSITIONS OF BAOBAB (Adansonia digitata L) FRUIT PULP AND SEED - Mamman, S.; Shuaibu, B. S.; Yusuf, J. A. (FUDMA JOURNAL OF SCIENCES, 2021)
This research presents the proximate and elemental compositions of Baobab fruit (Adansonia digitata L.) The proximate analysis gives the composition of the biomass in terms of gross components such as moisture, volatile matter, ash and fixed carbon. In this study, the proximate composition was determined using standard methods (AOAC) while the mineral content was analysed with the aid of an Atomic Absorption Spectrometry and Flame Photometry. Minerals are micronutrients that occur in foods in minute amounts but are very essential for body metabolism. The results revealed that Baobab seed and pulp are rich in crude protein, fat, carbohydrate and total ash contents. The high amount of total ash (3.15 0.05 %) and (4.65 0.55 %) present in the seed and pulp respectively suggests that they both possess high level of inorganic matter; thus, having high amount of minerals. The study also shows that Baoba seed and pulp have high economic value and are good and cheap sources of mineral element such as calcium, sodium, potassium, magnesium, copper and zinc. For these reasons, they can be incorporated into food supplements for both humans and animals, also could have industrial applications